Physiological energetics of juvenile clams Ruditapes decussatus in a high CO2 coastal ocean - Jose Fernandez-Reiriz, Ma; Range, Pedro; Anton Alvarez-Salgado, Xose; Labarta, Uxio (Marine Ecology Progress Series, 2011)
Effects of coastal ocean acidification, other than calcification, were tested on juvenile clams Ruditapes decussatus during a controlled CO2 perturbation experiment. The carbonate chemistry of natural (control) seawater was manipulated by injecting CO2 to attain 2 reduced pH levels (-0.4 and -0.7 pH units) as compared with the control seawater. After 87 d of exposure, we found that the acidification conditions tested in this experiment significantly reduced the clearance, ingestion and respiration rates, and increased the ammonia excretion rate of R. decussatus seeds. Reduced ingestion combined with increased excretion is generally associated with a reduced energy input, which will likely contribute to a slower growth of the clams in a future high CO2 coastal ocean. These results emphasize the need for management policies to mitigate the adverse effects of global change on aquaculture, which is an economically relevant activity in most coastal areas worldwide. Regional Ministry of Innovation and Industry of the Galician Government [08MDS018402PR]; Italian Ministry for Environment, Land and Sea; Foundation for Science and Technology of Portugal [ERA-CIRCLE/0004/2007]; European Commission